An effect of exercise with Nintendo Wii game on pulmonary function in healthy women - Mongkol, Sarayoot; Kangwanchaisin, Donlapha; Passapan, Sutida; Sengsrichan, Autcharra (Journal of Associated Medical Sciences, 2017)
Background: Regularly physical activities and exercises enhance pulmonary function. Nintendo Wii game is the one of the aerobic exercise games that can effect on cardiopulmonary function. Objectives: To evaluate an effect of exercise with Nintendo Wii game on pulmonary function in healthy women. Materials and methods: Forty healthy women subjects with 18-30 years were equally categorized into two groups; composed of the control group (n=20) and exercise group with Nintendo Wii game (n=20). The duration of exercise with Nintendo Wii game was 40 minutes and intensity with 60-75% maximal heart rate. After six weeks of exercise three times per week, pulmonary function was evaluated comparing to before exercise. Results: There was no any difference of all data between groups before exercise. After exercise, the results illustrated that %FEV1, F%VC, F%EV1/FVC, %PEF, and %FEF25-75%, were significantly increased in exercise group with Nintendo Wii game (p<0.05). Moreover, weight and body mass index (BMI) were also significantly decreased (p<0.05). Conclusion: Exercise with Nintendo Wii game for six weeks can increase pulmonary function in healthy women.